Determinantes da formulação de estratégia em indústrias emergentes: análise do setor de destilarias de cachaça artesanal de qualidade (AMPAQ) - Itamaury Teles de Oliveira (2004)
The emerging industry of artisanal cachaça, a quality sealed product, attained importance in the State of Minas Gerais/Brazil a little more than 15 years ago. During this time, many problems have arisen, but one of the main difficulties was diagnosed in a work executed by SEBRAE-MG technicians, indicating the absence of a strategic plan well fitted to thatnovel segment of the State economy. Therefore, the object of analysis of this work is composed by determinant factors for formulation of strategies for this embryonic industry - along with fragmentary structural characteristics seeking to obtain a solution for the detected problem. After an exhausting research in primary and secondary sources, asignificative volume of data about the industry of cachaça was gathered. The collected data was condensed in a questionnaire pondering 111 questions, previously grouped into different aspects such as: external environment; internal environment resources, and social/organizational cultures able to affect consumer behavior and the future panorama ofthe sector in the next five-10 years. This questionnaire was administered to specialists and producers of quality artisanal cachaça - in search for different perceptual views through the use of semantic differential technique, consistent in a series of bipolar evaluative scales of seven points. Each one of these scales presents two reverse concepts and resulted into valuable and voluminous data, which were quantitative treated with the use of parametric statistical procedures, such as standard deviation and coefficient of correlation. Initially, therespondents labeled the external factors, as treats or opportunities. After submitted to the causality matrix, the factors resulted in causal factors of treat and opportunity, reducing even more the preliminary questions involved in the analysis. Right after, the causal factors of threat and opportunity were separately submitted to a new matrix, in a way to classifythe projects by importance of factor, and by the possibility of administering it. Consequently, from the 99 existing possibilities, this method propitiated the reduction of strategic focus into six main projects, signalizing a consistent course for the emerging industry. Finally, in order for these emerging industries to make a quantitative jump towards sustainable growth, it was recommended the adoption of a strategy focused on differentiation, with is largely obtainable with the implementation of the projects defined as essential.